Efficacy of Cabbage Leaf versus Cooling Gel Pad or Diclofenac Gel for Patients with Knee Osteoarthritis: A Randomized Open-Labeled Controlled Clinical Trial - Thanapon Chobpenthai; Patcharapol Arunwatthanangkul; Wiriya Mahikul (Pain Research and Management)
Background. Osteoarthritis (OA) is one of the most common joint degeneration ailments adversely affecting the elderly population by impairing their physical movements and quality of life. This study aimed to establish the efficacy of cabbage leaf application in alleviating pain-related distress and positively improving OA conditions. Materials and Methods. Patients with moderate to severe (grades 3-4) OA by the Kellgren and Lawrence grading system with a poor to good Oxford Knee Score were selected for enrollment in this clinical trial. The participants were divided into three intervention groups: the cooling gel pad group for 20 minutes duration once a day (n = 20), the diclofenac gel group for 4 times a day (n = 20) as the control group (total n = 40), and the cabbage leaf group for 1-hour duration once a day (n = 20) as the experimental group (total n = 20). All trial participants were trained to record their Numerical Rating Scale (NRS) pain score and Oxford Knee Score and were advised to undergo weekly follow-ups and assessment of the outcome at 4 weeks. Data were analyzed by the paired t-test and analysis of variance (ANOVA). Results. The cabbage leaf group and cooling gel pad group showed a significant difference in both the Oxford Knee Score (p<0.001 in both groups) and NRS score (p<0.001 in both groups) before and after the intervention, by using the paired t-test. The three study procedures were found to be significantly different with respect to both the Oxford Knee Score (p=0.012) and NRS score (p<0.001), by using ANOVA. Conclusion. This study clinically demonstrated that cabbage leaf application and cooling gel pad application showed similar improvements in reducing OA symptoms in terms of the overall NRS score and Oxford Knee Score. Their therapeutic effectiveness was better than that of diclofenac gel.